Pengembangan Sistem Manajemen Kualitas Berbasis ISO 9001 di Industri Kecil - Alwi, Muhammad; Yunus, Kartini; Fahar, Andi Abustan; Kajang, Gideon; Paelongan, Ardi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
ISO 9001 is an international standard designed to improve an organization's quality management system to ensure operational efficiency and customer satisfaction. Small industries in Indonesia face various challenges in the implementation of these standards, including limited resources, lack of understanding, and resistance to change. Therefore, this study aims to develop a more adaptive ISO 9001 implementation strategy in small industries to improve their business competitiveness and sustainability. The research method used in this study is a literature study with a qualitative approach. Data is obtained from various academic sources such as scientific journals, research reports, and publications relevant to ISO 9001-based quality management systems in small industries. Data analysis was carried out using content analysis and thematic synthesis methods, in order to identify key challenges, success factors, and effective implementation strategies in small industries. The results of the study show that the main factors for the successful implementation of ISO 9001 in small industries are management support, employee training, technology utilization, and collaboration with external parties. Meanwhile, the main barriers found include the high cost of certification, lack of awareness of long-term benefits, and the complexity of documentation. Therefore, a more flexible approach, government incentives, and broader education programs are needed to ensure the successful implementation of ISO 9001 in small industries.